(untitled) (Scientific journal of the Fergana State University, 2023)
This article reveals the pragmatic functional aspects of the proverbs. Many of the functional definitions of the proverb have been theoretically substantiated by linguists as referring to the nature of the generalization of the situation or the recommendation, to take certain actions. The article also discusses the matter of the sayings.